Mary Ann (Gilbert) Hann with her niece Jessie Beatrice Gilbert (1893)
Mary Ann (Gilbert) Hann and her niece, Beatrice, daughter of Stephen Gilbert This collection contains copies made in 1998 of original photographs gathered by the Haystack Reunion Committee for publication in their booklet Haystack Reflections (1997).